2020
DOI: 10.1007/s11192-020-03726-9
|View full text |Cite
|
Sign up to set email alerts
|

Web mining for innovation ecosystem mapping: a framework and a large-scale pilot study

Abstract: Existing approaches to model innovation ecosystems have been mostly restricted to qualitative and small-scale levels or, when relying on traditional innovation indicators such as patents and questionnaire-based survey, suffered from a lack of timeliness, granularity, and coverage. Websites of firms are a particularly interesting data source for innovation research, as they are used for publishing information about potentially innovative products, services, and cooperation with other firms. Analyzing the textua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…First and foremost, not all companies have their own corporate website domain, which likely biases our web-based analysis results. Previous studies have shown that URL coverage of German companies is at 46% (Kinne & Axenbeck 2020). Especially among smaller firms the fraction without corporate URL is comparatively high.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…First and foremost, not all companies have their own corporate website domain, which likely biases our web-based analysis results. Previous studies have shown that URL coverage of German companies is at 46% (Kinne & Axenbeck 2020). Especially among smaller firms the fraction without corporate URL is comparatively high.…”
Section: Discussionmentioning
confidence: 90%
“…The extraction of relevant information from unstructured or semi-structured text data from corporate websites can be seen as particularly challenging here. At the same time, it promises a number of benefits, particularly in terms of granularity, timeliness, scope and cost of collection (Kinne & Axenbeck 2020). These benefits will also turn out to be key in this study.…”
Section: Related Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…However, neither are details on data collection nor on processing provided, and only a few approaches use web mining to scrape unstructured information from enterprise websites (e.g. [28]).…”
Section: Ecosystem Intelligence and Modellingmentioning
confidence: 99%
“…Instead, to collect data for ecosystem intelligence, a wide range of approaches are used, starting with analyzing enterprise websites to analyze the logo maps [29]. In [28], a web-mining approach is used to collect ecosystem data from enterprises. In [24], the authors combine a variety of independently created data sources on deals and alliance relationships, executive and funding relationships (EFRs), and public opinion and discourse (POD) to perform the analysis of ecosystems.…”
Section: Ecosystem Intelligence and Modellingmentioning
confidence: 99%